Balanced Scorecard to Attain Strategic Goal in the Manufacturing Industries in Kailali, District - Adhikari, Tek Bahadur (AMC Journal (Dhangadhi), 2024)
Balance Scorecard (BSC) is an emergent strategic management accounting technique that supports in making strategic planning and performances evaluation. This study’s primary objective is to assess decision makers’ familiarity with BSC and the extent of application by the managers to achieve their organizational strategic goals. The study used a descriptive and causal comparative research design. Primary data were collected through a structured 5 points likert scale questionnaire and 26 manufacturing companies in the Kailali district having higher annual turnover ware taken as sample using convenience sampling technique. The findings show that four dimensions of BSC (learning & growth, internal business process, Customer perspective and financial growth) have moderate correlation with each other. Decision makers are supposed to be familiar with BSC dimensions but overall impact of BSC- dimensions and their implication in the industries to attain strategic efficiency and effectiveness is insignificant. Decision-makers in all types of business organizations can be benefited from knowing the implications of BSC-dimensions. The strategic management accounting (SMA) community places a high priority on managerial staff members’ understanding about BSC.